Protection and Enforcement Challenges for Tattoo Copyrights - King, Yolanda M. (The Columbia Journal of Law & the Arts, 2016)
Good afternoon. I am going to discuss tattoos. And in twelve minutes I am going to try to summarize tattoo copyrights. I intend to combine discussion of a couple of articles I have written. I have written a series of articles on the copyrightability of tattoos, enforcement of tattoo copyrights, and another article on right of publicity, which, time permitting, I may mention briefly at the end of this presentation, but I am focusing on copyright and tattoos for today. So first I will briefly summarize my first article concerning copyrightability: it addresses the ambiguity regarding protectability of tattoos and the effects of the ambiguity on artists as well of their customers who are the tattoo-bearers. I ultimately conclude that tattoos are copyrightable, but I respond to some interesting arguments by David Nimmer, who is the author of a copyright treatise and was an expert retained by Warner Brothers in Whitmill v. Warner Brothers, which I will discuss in a moment.2 He raises some arguments and he, at least as of now, opines that tattoos are not copyrightable, and I think the opinion is problematic and it will be increasingly problematic as tattoos become more commonplace.